Hydrogen Treated Niobium Oxide Nanotube Arrays for Photoelectrochemical Water Oxidation. Issue 14 (17th November 2016) - Baik, Ji-Seon; Yun, Gun; Balamurugan, Maheswari; Lee, Sang Kwon; Kim, Jae-Hun; Ahn, Kwang-Soon; Kang, Soon Hyung
Abstract : Self-aligned Nb2 O5 nanotube (NT) arrays are grown by facile electrochemical anodization at 180°C with an applied bias of 10 V for 10 min in anhydrous glycerol electrolyte. Amorphous Nb2 O5 NT arrays can be transformed into pseudo-hexagonal Nb2 O5 NT arrays by annealing at 440°C for 20 min in ambient air. Hydrogen treatment of this film was conducted at 440°C for 20 min with flowing 4% H2 /96% Ar mixed gas. Hydrogen treatment causes no modification of crystalline properties and hydrogen-treated Nb2 O5 (denoted as H2 -Nb2 O5 ) NT arrays exhibit no apparent change in the optical bandgap, indicating negligible visible light absorbance. Only small changes in structural properties, such as pore diameter, wall thickness, and chemical state, are observed in the surface region of H2 -Nb2 O5 NT arrays. However, H2 -Nb2 O5 NT arrays exhibit a significant increase in electron concentration by the formation of oxygen vacancies, leading to significantly enhanced electronic conductivity. As a result, charge recombination reactions in the interfacial region between H2 -Nb2 O5 NT arrays and electrolyte are efficiently hindered, resulting in remarkably enhanced photocurrent density in the photoelectrochemical cell. The air-Nb2 O5 NT arrays exhibit a photocurrent density of only 0.11 mA/cm 2 at 1.0 VNHE, while H2 -Nb2 O5 NT arrays show a significantly increased photocurrent density up to 0.69 mA/cm 2 at 1.0 VNHE, a more than six-fold improvement in photoelectrochemical performance.